Implementasi Pendidikan Ramah Anak Berbasis Literasi Digital Sebagai Upaya Mengantisipasi Kekerasan Seksual Pada Siswa Sekolah Dasar Di Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi - Denatara, Eskar Tri (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The problem of sexual violence, one of the triggers of which is interaction on a number of social media platforms and the low level of digital literacy to be able to exercise self-control not to access pornographic content, has become a problem that in the last 2 years has become a problem that needs attention. Therefore, it is necessary to carry out massive education and use the suggestopedia method to implement Child-Friendly Education based on Digital Literacy. These efforts can be started at the level of elementary school students who are very vulnerable in order to anticipate and minimize the negative impacts of information technology and the internet. Remembering that adaptive learning to the times is a necessity for everyone, especially educators. The role of educators is very important in providing supervision and assistance to children in using digital technology. Without proper supervision or assistance, children and teenagers are very vulnerable to being exposed to negative content such as pornography and pornographic action or other cybercrime spread on the internet or other impacts from inappropriate use of information technology. The suggestopedia approach is the right choice because the information is conveyed using relaxation and concentration techniques which can help students manage subconscious sources and store the information obtained in deep memory. This effort is a new breakthrough carried out by paying attention to the thinking characteristics of children and adolescents combined with the concept of digital literacy. As a first step, this activity was carried out at SDN 10 Cibadak to develop a digital literacy community prototype, by presenting material and following up with monitoring digital literacy pocket books which could be implemented comprehensively in Sekarwangi Village, Cibadak District, Sukabumi Regency.